2018
DOI: 10.1016/j.ab.2017.11.012
|View full text |Cite
|
Sign up to set email alerts
|

15N CEST data and traditional model-free analysis capture fast internal dynamics of DJ-1

Abstract: Previous studies have shown that relaxation parameters and fast protein dynamics can be quickly elucidated from N-CEST experiments [1]. Longitudinal R and transverse R values were reliably derived from fitting of CEST profiles. Herein we show that N-CEST experiments and traditional modelfree analysis provide the internal dynamics of three states of human protein DJ-1 at physiological temperature. The chemical exchange profiles show the absence of a minor state conformation and, in conjunction withH-N NOEs, sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
4
6
0
Order By: Relevance
“…Two-dimensional (2D) 1 H- 15 N heteronuclear single quantum coherence (HSQC) spectra were collected at 37 °C as previously described 42,43 from uniformly 15 N labeled DJ-1 that was either reduced or overoxidized to Cys106-SO 3 − The 2D 1 H- 15 N HSQC spectra were collected on a 700 MHz Bruker Avance III spectrometer equipped with a 5 mm quadruple resonance QCI-P cryoprobe ( 1 H, 13 C, 15 N, and 31 P) with z -axis gradients. Order parameters ( S 2 ) were calculated from chemical exchange saturation transfer (CEST)-derived R 1 and R 2 relaxation rates and heteronuclear NOE values using FAST-Modelfree 44 as previously described 42 .…”
Section: Methodsmentioning
confidence: 99%
“…Two-dimensional (2D) 1 H- 15 N heteronuclear single quantum coherence (HSQC) spectra were collected at 37 °C as previously described 42,43 from uniformly 15 N labeled DJ-1 that was either reduced or overoxidized to Cys106-SO 3 − The 2D 1 H- 15 N HSQC spectra were collected on a 700 MHz Bruker Avance III spectrometer equipped with a 5 mm quadruple resonance QCI-P cryoprobe ( 1 H, 13 C, 15 N, and 31 P) with z -axis gradients. Order parameters ( S 2 ) were calculated from chemical exchange saturation transfer (CEST)-derived R 1 and R 2 relaxation rates and heteronuclear NOE values using FAST-Modelfree 44 as previously described 42 .…”
Section: Methodsmentioning
confidence: 99%
“…The reduced form of DJ-1 (DJ-1 Cys106-SH) can be oxidized to a sulfinic acid form (DJ-1 Cys106-SO 2 H) and a sulfonic acid form (DJ-1 Cys106-SO 3 H) in the presence of moderate or high oxidative stress paradigms (Figure 1). While the reduced and sulfinic DJ-1 forms are stable, the sulfonic form of DJ-1 is unstable and prone to aggregate formation [47,48,49].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidation also regulates DJ-1 subcellular distribution so that it can access binding partners localized to organelles, including stress granules and mitochondria (reviewed). However, further C106 oxidation to sulfonic acid form (i.e., C106-SO 3 H) owing to chronic oxidative stress destabilizes dimeric DJ-1 structure and leads to irreversible inactivation. , Here, we found that oxidation incompetent C106A mutant retains full tau chaperone activity, indicating that oxidation is not required for interaction with this specific client. These data predict that DJ-1 can protect full-length tau protein against aggregation under basal conditions in the absence of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%